Sosialisasi SNPMB dan KIP di SMKN 1 Kefamenanu - Adeodata Laniria Charla Barros Mbiri; Fridus Bria; Yosef Kristoforus Taekab (Indonesian Journal Publisher, 2024)
The National Selection for New Student Admissions (SNPMB) at state universities (PTN) in 2024 based on Permendikbudristek Number 62 of 2023 concerning new student admissions at PTNs has undergone policy changes so that one solution is to socialize SNPMB to prospective students in the 3T area of Timor Island. This socialization activity was facilitated by the University of Timor with one of the loci being SMKN 1 Kefamenanu. The methods used are preparation, implementation and evaluation. In the preparation stage, the legality of activities is carried out, preparation and discussion of project procedures, as well as an initial survey. At the implementation stage, socialization and assistance for KIP (Indonesian smart card) registration was carried out, then at the evaluation stage, understanding of the material that had been provided was measured. As a result of this activity, students at SMKN 1 Kefamenanu have understood the 2024 SNPMB mechanism and the suggestions from this activity will be taken into account in further socialization activities which are targeted not only at prospective students but also involve parents so that the information obtained can be used as material for consideration in facilitating children's education. his son.